The influence of personality towards employee's performance at Hospital Raub, Pahang / Nor Azeera Abd Rahim - Abd Rahim, Nor Azeera (Faculty of Business and Management, 2018)
The purpose of this research study to determine the influence of personality towards the employee's performance. According to the personality, consist of five elements that able for independent variables which are Conscientiousness, Agreeableness, Neuroticism, Openness to Experience and Extraversion (CANOE). Hospital Raub was provided the services for the customers or patients that need the services or treatments. However, the Department of Management provided the services for the staffs at the Hospital Raub which are Medical Officer, Medical Assistant, Staff Nurses and others staffs. Furthermore, for this study, the researcher using the descriptive statistic method to key in the questionnaire to gets the information and using the Statistical Package in the Social Science Software (SPSS) version 21. From the findings, the researcher was found that the independent variables have a relationship with the dependent variable. Other than that, the researcher also made the recommendation for the organization to maintained the good personality and the employees may know about them strengthens or weakness. The researcher also made a recommendation for the future research to improve or using the new the techniques